PELAKSANAAN PROMOSI DI OBJEK WISATA DANAU BANDAR KHAYANGAN LEMBAH SARI KOTA PEKANBARU - Nuryanti Manalu; Syofia Achnes (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Riau Province has a number of potential and tourist attraction is quite large. There are several attractions in Pekanbaru City which has the charm and attractiveness of each that can be developed to allow tourists to visit the city of Pekanbaru. Tourism attractions Khayangan Valley Sari has been expected to develop into one of the mainstay sources to increase the original revenue area Pekanbaru. Tourism Object of Bandar Khayangan Lake Sari Valley is located in Kel.Limbungan, Kec.Rumbai which is not far from the center of Pekanbaru City. The attraction of this tourist attraction is the atmosphere is very beautiful and cool. It is suitable for tourists who are already saturated with urban hustle and bustle. In the Tourism Object of Bandar Khayangan Lake Sari Valley is located in Kel.Limbungan, Kec.Rumbai this also has a calm atmosphere so it is very interesting to visit. This study aims to: (1) Know how the implementation of promotions made; (2) What constraints faced in promoting the attractions of Bandar Khayangan Lake Lembah Sari Pekanbaru City. In this research research method that I use quantitative method with descriptive approach. Technique of collecting data in this research use observation, interview, koesioner and documentation. Based on the results of research that has been done, shows that the implementation of promotions made by way of advertising, personal seling and public relations at Objects of Lake Bandar Khayangan Lembah Sari Pekanbaru still poor. The obstacles in carrying out promotion in Tourism Object of Bandar Khayangan Lake Lembah Sari Pekanbaru City is the problem of limited costs and still lack of human resources experts in this field of promotion.Keyword : Advertising, Personal selling, Public Relation